Incidence and indications of LSCS among Doctors Community of Chattogram - Malik, Adiba; Nessa, Kamrun; Begum, Yasmin Ara; Uddin, M Jalal; Sultana, Aklima; Ferdous, Nasrin; Bardhan, Purabi (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Lower segment caesarean section (LSCS) is a surgical intervention, which is carried out to ensure the safety of mother and baby when vaginal delivery is not possible or when danger to mother and baby would be greater with vaginal delivery. This study is designed to identify indication of LSCS and detect complications if any among the respondents. Materials and methods: Cross sectional descriptive study where 95 female doctors of Chattogram were selected by convenient sampling without knowing their mode of delivery and if it is LSCS then indication of LSCS , maternal and neonatal complications were noted. Results: Age of the respondents at the time of interview were noted and most of them were between 31- 40 years 52 (55%), regarding income most of them between 100000 -200000 42(44%) most of the delivery occurred in the private clinics 92 (70%) regarding mode of delivery, LSCS was 92 (70%) vaginal delivery 40 (30%) regarding indications of LSCS most common was repeat caesarean section 27 (29%) and second common was LSCS due to maternal interest 18 (20%) and others were severe preeclampsia 10 (11%) fetal distress 08(09%) placenta previa, Diabetes with big baby, cephalopelvic disproportion, PROM with non progression of labour. PPH was the most common complication 05 (63%), next was paralytic ileus 02 (25%) and left ventricular failure 01 (12%). Common neonatal comoplications were low birth weight baby 904 (40%), prematurity 03 (30%) and birth asphyxia 03 (03%). Conclusion: LSCS is a major surgical procedure for delivery. Inspite of its low maternal morbidity and mortality due to improved surgical technique, modern aneasthetic skill and availability of blood and blood products, still it carries a slightly greater risk in subsequent pregnancy, so we should be rational in doing primary caesarean section. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 37-40